1976
DOI: 10.1002/iroh.19760610602
|View full text |Cite
|
Sign up to set email alerts
|

Boring by Macro‐organisms in the Coral Montastrea annularis on Barbados Reefs

Abstract: The fauna boring into Montastrea annularis includes sponges" bivalves, sipunculid and polychaete worms and barnacles. Sponges.and spionid polychaetes are most important in hard tissue destruction and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 26 publications
(16 reference statements)
3
48
0
Order By: Relevance
“…These, are attached to the coral bases, bore the skeleton, or live over or under the colonies (McCloskey, 1970;Young, 1986;Arvanitides and Koukouras, 1994). Many authors have emphasised the destructive impact of the endolithic fauna on coral colonies, a process known as bioerosion (Hein and Risk, 1975;MacGeachy and Stearn, 1976;Hutchings, 1986;Kiene and Hutchings,1992); among the studies with a more specific focus, those on sponges (Rützler, 1975), molluscs (Hadfield, 1976;Morton, 1983;Moretzsohn and Tsuchyia, 1992), polychaetes (Kohn and Lloyd, 1973;Arvanitides and Koukouras, 1994;Nogueira, 2000), and sipunculids (Rice, 1976;Rice and Macintyre, 1982) should be noted.…”
Section: Androrqlhv Ri 0xvvlvplold Klvslgd Zhuh Froohfwhg Lq Irxu Vrxwkmentioning
confidence: 99%
See 1 more Smart Citation
“…These, are attached to the coral bases, bore the skeleton, or live over or under the colonies (McCloskey, 1970;Young, 1986;Arvanitides and Koukouras, 1994). Many authors have emphasised the destructive impact of the endolithic fauna on coral colonies, a process known as bioerosion (Hein and Risk, 1975;MacGeachy and Stearn, 1976;Hutchings, 1986;Kiene and Hutchings,1992); among the studies with a more specific focus, those on sponges (Rützler, 1975), molluscs (Hadfield, 1976;Morton, 1983;Moretzsohn and Tsuchyia, 1992), polychaetes (Kohn and Lloyd, 1973;Arvanitides and Koukouras, 1994;Nogueira, 2000), and sipunculids (Rice, 1976;Rice and Macintyre, 1982) should be noted.…”
Section: Androrqlhv Ri 0xvvlvplold Klvslgd Zhuh Froohfwhg Lq Irxu Vrxwkmentioning
confidence: 99%
“…According to Fauchald and Jumars (1979), the feeding guilds of the most representative families of polychaetes in the present study observed suggested that they were very important on these communities, controlling populations of microcrustaceans, feeding on suspended materials, and on detritus and bacteria entrapped in coral mucus. Other well known group of endolithic animals is that of bivalves, whose importance should be seen in terms of making great holes at the corals bases, causing their dislodgement from the substrate (MacGeachy and Stearn, 1976;Hutchings, 1986), rather then in the number of specimens; another role of them is increasing the available space for larval settlement of other borers (McCloskey, 1970). The most studied group of boring bivalves is the subfamily Lithophaginae (family Mytilidae), in which this habitat has evolved from earlier forms attached to the substrate (Yonge, 1955).…”
Section: Wdwlvwlfdo Dqdo\vlvmentioning
confidence: 99%
“…We found members of several polychaete families known for boring; Eunicidae, Sabellidae and Spionidae, represented here by the genus Polydora (Haigler 1969;MacGeachy and Stearn 1976;Davies and Hutchings 1983). Previous studies have shown that boring polychaetes can weaken corals (Wielgus et al 2006) and have deleterious impacts on bivalves and gastropods of economic significance.…”
Section: Polychaetesmentioning
confidence: 66%
“…We could not identify the sipunculid genus we found; however, the specimens and their boreholes very much resemble examples of the genus Phascolosoma given by Rice (1969) and MacGeachy and Stearn (1976). They assume a combination of chemical and mechanical drilling for sipunculids.…”
Section: Sipunculidamentioning
confidence: 68%
See 1 more Smart Citation